Establishment of a Percutaneous Coronary Intervention Registry in Vietnam: Rationale and Methodology - Vu, Hoa T. T.; Nguyen, H.T.T.; Pham, H.M.; Do, L.D.; Nguyen, Q.N.; Norman, Richard; Huxley, Rachel; Pham, Ngoc M.; Lee, Crystal M. Y.; Reid, Christopher (2020)
Copyright: © 2020 The Author(s).